2016
DOI: 10.1002/anie.201601447
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Promiscuous Non‐Heme Iron Halogenase in Ambiguine Alkaloid Biogenesis: Implication for an Evolvable Enzyme Family for Late‐Stage Halogenation of Aliphatic Carbons in Small Molecules

Abstract: The elucidation of enigmatic enzymatic chlorination timing in ambiguine indole alkaloid biogenesis led to the discovery and characterization of AmbO5 protein as a promiscuous non-heme iron aliphatic halogenase. AmbO5 was shown capable of selectively modifying seven structurally distinct ambiguine, fischerindole and hapalindole alkaloids with chlorine via late-stage aliphatic C-H group functionalization. Cross-comparison of AmbO5 with a previously characterized aliphatic halogenase homolog WelO5 that has a rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 25 publications
3
82
0
6
Order By: Relevance
“…This observation provided a molecular basis for the altered structural diversity of hapalindole-type alkaloids between the two welwitindolinone producers. The extreme sequence similarity (95% identical) between WelO5* and WelO5 allowed us to trace the origin of this observed specificity difference to 11 amino acid residues at a C-terminal sequence motif, initially discovered in the comparative characterization of WelO5 and AmbO5 [18]. This further confirms the functional significance of this conserved sequence motif in this new halogenase family that may guide the rational engineering and evolution of these proteins for biocatalyst application.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…This observation provided a molecular basis for the altered structural diversity of hapalindole-type alkaloids between the two welwitindolinone producers. The extreme sequence similarity (95% identical) between WelO5* and WelO5 allowed us to trace the origin of this observed specificity difference to 11 amino acid residues at a C-terminal sequence motif, initially discovered in the comparative characterization of WelO5 and AmbO5 [18]. This further confirms the functional significance of this conserved sequence motif in this new halogenase family that may guide the rational engineering and evolution of these proteins for biocatalyst application.…”
Section: Introductionsupporting
confidence: 57%
“…The biochemical characterizations of WelO5/AmbO5 chimera revealed that a C-terminal sequence motif plays a role in the substrate tolerance and provided insights into the origin of substrate promiscuity in this family of proteins [18]. In this work, we report the characterization of the third WelO5-type protein, WelO5*, for the biogenesis of welwitindolinones in H. welwitschii IC-52-3.…”
Section: Introductionmentioning
confidence: 98%
“…266 An NHFe halogenase is also present in this pathway (AmbO5) that shares ~79% sequence identity with WelO5 and has recently been shown to exhibit chlorination activity on a variety of deschloroambiguines. 267 …”
Section: Non-heme Iron-dependent Halogenasesmentioning
confidence: 99%
“…Studies on the substrate scope of NHFe halogenases acting on freestanding substrates, WelO5 and AmbO5, revealed a relaxed substrate specificity of AmbO5 towards a variety of hapalindole-type molecules. 267 In addition, the substrate scope could be modulated by generating a variety of WelO5/AmbO5 chimeras, all while retaining regio- and stereoselectivity.…”
Section: Non-heme Iron-dependent Halogenasesmentioning
confidence: 99%
“…51 Other examples have been described, 48 including the non-heme halogenase Amb05 which catalyzes the regioand stereoselective halogenation of an amazingly wide range of alkaloids and other compounds at aliphatic CH-positions. 52 Nevertheless, screening many enzymes of a given type does not routinely lead to the regioselectivity that the researcher may need, which means that alternative approaches are required. Protein engineering of an FDH by rational site-specific mutagenesis was first reported in 2011 in which mutant F103A of the halogenase PrnA was found to change the strict 7-selectivity of WT to a 2 : 1 mixture of the 7-and 5-chlorinated products.…”
Section: Engineering Site-selectivity Of Halogenasesmentioning
confidence: 99%